SYNTACTIC TRANSLATION STRATEGIES IN ENGLISH-INDONESIAN ASEAN CHARTER - Allika Risa Haya; Rita Sutjiati Djohan (Universitas Gunadarma, 2022)
This research was carried out to analyze the syntactic translation strategies applied in English-Indonesian ASEAN Charter document. This research also aimed to find out which strategy is most often used and its possible reason. This research is based on the theory of syntactic strategies by Andrew Chesterman (2016, p. 91). The researcher used a qualitative method. The data used in this research is in the form of text on the ASEAN Charter document. This research showed that there are 8 syntactic strategies used in the English-Indonesian ASEAN Charter. Those are literal translation (33%), loan and calque (31%), transposition (8%), unit shift (14%), phrase structure change (8%), clause structure change (0,38%), level shift (1%), and scheme change (5%). Literal translation is the most widely applied in this research because this strategy is an appropriate strategy to translate a legal document.